2016
DOI: 10.1038/srep27521
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen and parathyroid hormone alleviate lumbar intervertebral disc degeneration in ovariectomized rats and enhance Wnt/β-catenin pathway activity

Abstract: To investigate the mitigation effect and mechanism of oestrogen and PTH on disc degeneration in rats after ovariectomy, as well as on Wnt/β-catenin pathway activity, thirty 3-month-old rats were ovariectomized and divided into three groups. Ten additional rats were used as controls. Eight weeks later, the rats were administered oestrogen or PTH for 12 weeks, and then discs were collected for tests. Results showed that nucleus pulposus cells in the Sham group were mostly notochord cells, while in the OVX group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“… 46 iPTH injection improves the adjacent segment disc degeneration by enhancing lumber fusion 47 and alleviates disc degeneration in ovariectomized osteoporotic mice by up-regulation of Wnt/β-catenin pathway. 48 In this study, we demonstrate that PTH1R is expressed in the NP cells of notochordal origin to maintain disc homeostasis particularly during aging by directly activating TGF-β signaling in NP cells in addition to its expression in vertebral bodies and endplates. The results suggested that expression of PTH1R in disc cells promotes the mobility of amphibians in their adaptation to terrestrial life from aquatic vertebrates.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“… 46 iPTH injection improves the adjacent segment disc degeneration by enhancing lumber fusion 47 and alleviates disc degeneration in ovariectomized osteoporotic mice by up-regulation of Wnt/β-catenin pathway. 48 In this study, we demonstrate that PTH1R is expressed in the NP cells of notochordal origin to maintain disc homeostasis particularly during aging by directly activating TGF-β signaling in NP cells in addition to its expression in vertebral bodies and endplates. The results suggested that expression of PTH1R in disc cells promotes the mobility of amphibians in their adaptation to terrestrial life from aquatic vertebrates.…”
Section: Discussionmentioning
confidence: 65%
“…During aging or disc degeneration, endplates become calcified and sclerotic, leading to less efficient diffusion of nutrients in support for discs. 56 , 57 iPTH will stimulate osteoclast resorption of the sclerotic endplates and induce native bone formation through remodeling, 48 and the process likely improves their diffusion property for the disc. Similarly, iPTH stimulates bone remodeling and improves bone quality for the vertebral bodies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Luo et al ( 6 ) identified a close relationship between IDD and osteoporosis in ovariectomized rats, and speculated that the mechanism involved was related to the integrity and function of adjacent structures of intervertebral discs in the spine. Adjacent segment disc degeneration is very common in women with osteoporosis, thus indicating that osteoporosis might represent one of the causative agents of IDD ( 7 ). Research has shown that the endplate of patients with osteoporosis is under high pressure and that this can cause endplate calcification.…”
Section: Introductionmentioning
confidence: 99%
“…PTH is also known to regulate the synthesis and metabolism of intervertebral disc cells and inhibit potential calcification molecules via the mitogen-activated protein kinase (MAPK) and protein kinase A (PKA) signaling pathways ( 9 ). It has also been reported that PTH cannot only promote anabolic metabolism, but can also inhibit degradation of the extracellular matrix within intervertebral discs ( 7 ). Indeed, animal experiments have established that PTH can relieve disc degeneration in rat models of osteoporosis ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several signaling pathways have been reported to be involved in IDD, including the Wnt/β-catenin, the P53/P21, the interleukin, and the tumor growth factor-β pathways (26,(29)(30)(31)(32)(33). These signaling pathways have important roles in regulating IDD.…”
Section: Discussionmentioning
confidence: 99%